Completing the bedrock mapping of southern Baffin Island, Nunavut; plutonic suites and regional stratigraphy - Weller, O. M.; Dyck, B J; St-Onge, Marc R.; Rayner, N.; Tschirhart, V (Canada-Nunavut Geoscience Office, 2015)
This paper summarizes the field observations and initial interpretations following eight weeks of regional and targeted bed- rock mapping on south-central Baffin Island, Nunavut. The 2015 field campaign completes a two-decade mission to update the geoscience knowledge for the whole of Baffin Island south of latitude 70°N. The bedrock in the area is dominated by a Paleoproterozoic metaplutonic suite, ranging in composition from gabbro to syenogranite, with crosscutting relations indi- cating a progression from mafic to silicic magmatism. Phase-equilibria modelling reveals that the prevailing upper-amphi- bolite– to lower-granulite–facies metamorphic conditions overlap the stability limits of magnetite and orthopyroxene for a typical granitoid bulk composition, which is consistent with field observations of the discontinuous presence of both phases throughout the map area. This result is also consistent with regional aeromagnetic data that show complex structures within relatively homogeneous map units, which are primarily attributed to variations in the abundance of magnetite. The granitoid rocks are interpreted as part of the middle Paleoproterozoic Cumberland Batholith. Metasedimentary rocks, including quartzite, pelite, marble and metagreywacke, are present as enclaves and screens within and between plutonic bodies. An examination of the ‘ghost’stratigraphy suggests that the metasedimentary rocks through- out most of the map area can be correlated with the middle Paleoproterozoic Lake Harbour Group, except in the northeast, where the unique presence of greywacke suggests a middle Paleoproterozoic Piling Group affinity. This transition in strata is consistent with the proposal that a middle Paleoproterozoic tectonic suture (the Baffin suture) associated with the Trans- Hudson Orogen runs through Cumberland Sound. Completion of the bedrock mapping in southern Baffin Island indicates that the region offers a world-class exposure of a reworked Paleoproterozoic convergent margin, which affords valuable in- sight into a variety of magmatic and tectonic processes that can be applied to younger collisional belts